2013
DOI: 10.4172/2161-0673.1000123
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Professionalism among Physical Therapists in India- A National Cross-Sectional Survey

Abstract: Background and purpose: The American Physical Therapy Association (APTA) developed the core values of leadership, administration, management and professionalism for physical therapists. The aim of this study was to assess the levels of professionalism among physical therapists in India. Materials and methods:This cross-sectional study was done using a survey questionnaire-Professionalism In Physical Therapy-Core Values (PPTCV) instrument that consisted of sample indicators for each of the seven core values-acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
2
2
2
Order By: Relevance
“…The study findings indicated that neither age of the participants nor gender has been reported to have an effect on the levels of competency. These results agreed partly with Kumar et al (10) findings who stated that a relatively higher level of professionalism was observed with increase in age of the PTs, while gender didn't show the same effect.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The study findings indicated that neither age of the participants nor gender has been reported to have an effect on the levels of competency. These results agreed partly with Kumar et al (10) findings who stated that a relatively higher level of professionalism was observed with increase in age of the PTs, while gender didn't show the same effect.…”
Section: Discussionsupporting
confidence: 91%
“…The total scores of the standards were categorized into six levels: < 15% = very low, 16-30% = low, 31-45% = moderate, 46-60% = fair, 61-75% = high, >75% = very high. The percentiles were obtained from calculating proportion of obtained scores with respect to total achievable scores (10) .…”
Section: Statistical Methods and Data Analysismentioning
confidence: 99%
“…2 The scores of altruism (17.98±3.78) are similar to the above study (12.54±1.12) which is indicative that this domain needs to be focused on properly. 2 According to Marques-Sule students do not consider values such as altruism, diligence, empathy and compassion compulsory for practicing the profession. 3 This lack of awareness of altruism and compassion for practice of any profession is a global problem.…”
Section: Resultssupporting
confidence: 81%
“…The mean score obtained in this study is 268.65±33.1/345 whereas in the study conducted by Kumar et al, the mean score obtained by PG students was 163.30±5.40. 2 More than 50% difference was found in the scores of accountability (40.36±6.50) compared to the study conducted by Kumar et al (18.06±1.49) which may be due to the sample size difference & the fact that the current study has been carried out in the PG students of one city whereas the former study was carried out on a national level. 2 The scores of altruism (17.98±3.78) are similar to the above study (12.54±1.12) which is indicative that this domain needs to be focused on properly.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation